FAKTOR RISIKO KEJADIAN WASTING PADA REMAJA PUTRI (Studi Kasus pada Siswi Umur 13-15 Tahun di SMP Walisongo 1 Semarang Tahun 2017) - Erika Kusuma Hastuti; Siti Fatimah Pradigdo; Suyatno Suyatno (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The result of Basic Health Research in 2013 showed that the prevalence of wasting in adolescents aged 13-15 years old reached 11.1%. This figure indicates that wasting becomes a community nutritional problem (> 5%). The purpose of this study is to know the factors associated with the incidence of wasting in adolescent aged 13-15 years in Walisongo 1 Junior High School Semarang. This research is an explanatory research with case control design. Subjects were 60 female students consisting of 30 cases and 30 controls, then analyzed using chi-square test. Nutritional status data were measured using IMT/ Uindicator, body image data, peers, mass media and pocket money collected using questionnaire, and daily intake collected with recall. The results showed that body image (p-value = 0.121; CI = 0,158-1,249; OR = 0,444) it’s a protective factor, peers (p-value = 0,069; CI = 0,411-3,204; OR = 1,147) and pocket money (p = value = 0,795; CI = 0,414-3,166; OR = 1,144) are not a risk factor, mass media (p-value=0,009, CI=1,387-12,270; OR=4,125); energy consumption level (P-value = 0,000, CI = 4,808-121,625; OR = 24,182) and protein consumption level (p-value = 0,024; CI = 1,150-12,713; OR = 3,824) are risk factor. This study recommends teenagers to reduce exposure advertisment in media mass and increase the consumption of food that contain energy and protein.